Compact, Angled Polarization Splitter: Characterization of Broadband Performance and Fabrication Tolerance - Yannick D'Mello; Eslam El-Fiky; James Skoric; Amar Kumar; Michael Hui; Yun Wang; Laurent Guenin; David Patel; David V. Plant (IEEE Photonics Journal)
We propose and experimentally demonstrate a broadband polarization beam splitter on the silicon-on-insulator platform using the concept of multimode interference. The angle between the input waveguide and the multimode interferometer (MMI) was optimized in order to extract the images corresponding to the fundamental transverse electric (TE) and transverse magnetic (TM) polarizations from a single, compact MMI. By changing the direction of propagation, the input angle enabled the addition of a parallelepiped to facilitate exclusively TM collection above the MMI, therefore eliminating the need to cascade successive MMIs. The MMI was tapered to improve coupling at the ports. The design allowed for a compact geometry with a length of 67.5 μm and width of 4 μm, while maintaining a feature size comparable to the waveguide width. The design was experimentally characterized over 72 parameter variations, including input angle, output TM and TE port positions, and bend radius of the output TE waveguide. The performance was consistent over the 100 nm wavelength range of 1500–1600 nm, with an average insertion loss of 2 dB. The device maintained an extinction ratio of at least 13.96 and 11.45 dB in the C-band for the TE and TM polarizations, respectively.